Design and in-field testing of a multi-level system for continuous subjective occupant feedback on indoor climate. (February 2021) - Lassen, Niels; Josefsen, Terje; Goia, Francesco
Abstract: Information gaps between the building and the occupant often lead to sub-optimal building performance, impairing the efforts towards more sustainable buildings. New information and communication technology creates new possibilities to reduce this gap, enhancing the interaction between occupants and their environments while providing operational usage data. Continuous subjective feedback from occupants can be used directly to improve building operation and tuning, but may also inform building design and research applications. In this study, we perform a literature study of existing systems for continuous subjective occupant feedback (CSOF) regarding indoor climate. Based on our findings we design a multi-level CSOF system which gathers occupant feedback regarding complaints, control actions and satisfaction evaluations. We qualitatively evaluate the systems in field tests in three buildings with a total of 63 un-informed occupants for a total of 167 days, and identify a series of "practical" lessons learned. Occupant opinions were collected through regular surveys and a final focus group interview. Deliberate temperature interventions were performed in two of the buildings. The experiments collected a total of 56 complaints, 133 control actions via smartphone, 1344 control actions via manual control and 311 satisfaction evaluations. The occupants provided useful data to the system through their daily interaction with it. They expressed satisfaction with the increased level of interaction and control they were offered through the system and showed a preference for solutions that give an immediate feedback to their actions and have a simple and intuitive interface. Graphical abstract: Image 1 Highlights: We identified though a literature study research gaps on continuous subjective occupant feedback. We designed a non-intrusive occupant feedback system with off-the-shelf components. Field tests were performed in 3 buildings with 63 un-informed occupants for a total of 167 days. Complaints, control actions, and satisfaction evaluations were collected under real operations. Usability is crucial, simple interfaces giving immediate response are preferred.